FINANCIAL AND DIGITAL LITERACY EMPOWERMENT FOR MSME DEVELOPMENT IN KAMPUNG KUE RUNGKUT SURABAYA - Aloisius Hama; Annisah Febriana; Hafidulloh; Dani Rohmati; Mersiana Varia Juita (Suluh Adiluhung Publisher (SAPub), 2026)
The development of digital technology and increasing business competition require Micro, Small, and Medium Enterprises (MSMEs) to improve their financial management and digital capabilities in order to maintain business sustainability and competitiveness. However, many MSME actors, particularly community-based enterprises, still face limitations in financial literacy and digital literacy. This community service program aimed to enhance financial literacy and digital literacy among MSME actors in Kampung Kue Rungkut Surabaya. The program was implemented through several stages, including observation, needs assessment, educational sessions, practical training, mentoring, and evaluation activities. The financial literacy component focused on transaction recording, cash flow management, production cost calculation, budgeting, and pricing strategies. Meanwhile, the digital literacy component emphasized social media marketing, digital branding, product photography, online communication, marketplace utilization, and digital payment systems. The results showed significant improvements in participants’ understanding and skills regarding financial management and digital technology utilization. Participants became more capable of recording financial transactions, separating personal and business finances, calculating production costs accurately, and managing business cash flow. In addition, participants demonstrated increased confidence in using social media for product promotion, creating digital content, and communicating with customers through online platforms. Overall, the program successfully strengthened managerial and digital competencies among MSME actors and encouraged more adaptive, innovative, and sustainable business practices in Kampung Kue Rungkut Surabaya.